The Fight Against Hoax: An Explorative Study towards Anti-Hoax Movements in Indonesia - Mufti Nurlatifah (Ikatan Sarjana Komunikasi Indonesia, 2019)
False information or â€œhoaxâ€ related to political, economic, religious, cultural, even health issues has become a cause for concern for many people. It is feared that the massive proliferation of hoax-related issues in our public sphere, both in the media and daily interaction, will lead to conflicts if itâ€™s not handled properly. This fear has prompted some movements to fight hoax in Indonesia. The fight against hoax is conducted by many sides, both from government and non-government, in many forms. The Ministry of Communication and Informatics, the Police of the Republic of Indonesia, and the Indonesian Anti-Hoax Citizens have launched a number of anti-hoax movements by publishing information considered hoax. Besides, there are also some other movements to fight hoaxes, such as HoaxAnalyzer by students of the Bandung Institute of Technology (ITB) and Apps application by the Islamic organization Muhammadiyah. Â On the global scale, the movement against hoax has been led by Google through Google News Lab and First Draft. The movement to fight hoax is conducted by combining technology and humanâ€™s cognition to verify the information. Discussion in this research will explore some anti-hoax movements in society. This study aims to map anti-hoax movements in Indonesia. The mapping is intended not only to explore the form of the movements and the methods they use to fight hoax but also to see how effective the movements are to fight hoax in Indonesia.